2017
DOI: 10.1038/onc.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

CTCF genetic alterations in endometrial carcinoma are pro-tumorigenic

Abstract: CTCF is a haploinsufficient tumour suppressor gene with diverse normal functions in genome structure and gene regulation. However the mechanism by which CTCF haploinsufficiency contributes to cancer development is not well understood. CTCF is frequently mutated in endometrial cancer. Here we show that most CTCF mutations effectively result in CTCF haploinsufficiency through nonsense mediated decay of mutant transcripts, or loss-of-function missense mutation. Conversely, we identified a recurrent CTCF mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 48 publications
6
58
1
Order By: Relevance
“…These data and our previous studies indicated that CTCF dosage is critical for its tumour suppressive functions [25], [32], however CTCF haploinsufficiency has not been definitively modelled in vitro. To address this, we used CRISPR/Cas9-directed genome editing to induce genetic lesions in K562 cells (Supplementary Figure 1A), which we previously verified to contain wild type CTCF alleles using Sanger sequencing [25].…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…These data and our previous studies indicated that CTCF dosage is critical for its tumour suppressive functions [25], [32], however CTCF haploinsufficiency has not been definitively modelled in vitro. To address this, we used CRISPR/Cas9-directed genome editing to induce genetic lesions in K562 cells (Supplementary Figure 1A), which we previously verified to contain wild type CTCF alleles using Sanger sequencing [25].…”
Section: Resultscontrasting
confidence: 43%
“…Genetic lesions in CTCF, whether heterozygous deletion, nonsense, frameshift or even missense zinc finger (ZF) mutations, can all result in CTCF haploinsufficiency. In endometrial cancer, CTCF mRNA transcripts expressed from alleles containing nonsense or frameshift mutations are subjected to nonsense-mediated decay [30], [32]. Somatic missense mutations in residues critical for CTCF ZF binding to DNA can result in selective loss of binding to some CTCF target sites, but not all [26], indicating the functional implications of incomplete loss of CTCF binding in cancer is unclear.…”
mentioning
confidence: 99%
“…All of those transcription factors (except CEBPA) are known to be expressed in the glands of the human endometrium. CTCF can function as a transcriptional activator, a repressor, or an insulator and regulates cell polarity of the GE (55). FOSL2 is a component of the activator protein 1 transcription factor complex and regulates cell proliferation, differentiation, and transformation, but its role in uterine glands is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, frequent mutations of CTCF motifs in the vicinity of oncogenes have been reported in colorectal, liver and esophageal cancer (58, 59). Furthermore, the CTCF protein and its associated boundary factor cohesion are both subject to recurrent mutation in multiple tumor types (60–63). CTCF haploinsufficiency has also been shown to promote tumor formation in mice (64).…”
Section: Epigenetic Plasticity: Dna Methylation and Disruption Of Oncmentioning
confidence: 99%